Analysis of the Effectiveness of Information and Communication Technology in the Sustainable Urban Development Process (Case study: West Urban Areas of Kermanshah Province) - mohtaram mirzaeian; bijan rahmani; majid shams; abbas malekhoseini (تحقیقات کاربردی علوم جغرافیایی)
The real world has been created of extremely complex mosaics. The regional analysis entails the study of the mechanism of the processes involved in systems that are capable to explain the emergence, growth and decline of a region, but like any other geographic research, doing comparison in such a study is inevitable. The cities of the world are now the homes of more than half of the world’s population. Perhaps the most important global challenge of our age is to make sure that whether the planet remains habitable and provides sufficient resources for future generations. In this study, a descriptive-analytic method has been used to analyze the effects of information and communication technology in urban sustainable development in west urban areas of Kermanshah province. The statistical population of the study consisted of 184642 people that 386 individuals were randomly selected as the sample. The required data were collected by documentary-library method and field study and analyzed and processed using SPSS software and variance analysis model. The results showed that the cities of Qasr-eShirin, Gilan-e Gharb, KerendGharb, Sarpol-e Zahab and Islam AbadGharb obtained the first to fifth ranks respectively in terms of the affectability from information and communication technology in sustainable urban development.